Cardiovascular Reactivity to Mental Stress and Adverse Cardiovascular Outcomes in Patients With Coronary Artery Disease - Kasra Moazzami; Samaah Sullivan; Maggie Wang; Alexis K. Okoh; Zakaria Almuwaqqat; Brad Pearce; Amit J. Shah; Yan V. Sun; Yi‐An Ko; Paolo Raggi; J. Douglas Bremner; Viola Vaccarino; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Acute psychological stress may induce physiological changes predisposing individuals to adverse health outcomes through hemodynamic and vascular effects. We studied the association between the aggregated stress‐induced changes in hemodynamic and vascular function tests with adverse cardiovascular outcomes in patients with coronary artery disease, after adjusting for sociodemographic and clinical factors. Methods and Results Individuals with stable coronary artery disease from 2 prospective cohort studies were studied. Hemodynamic reactivity, changes in endothelial function, and vasoconstriction during mental stress were evaluated using changes in rate‐pressure product, brachial artery flow‐mediated vasodilation, and peripheral arterial tonometry, respectively. A cardiovascular reactivity risk score was calculated by allotting 0 to 3 points for each quartile of increasing abnormality for each of the 3 reactivity responses and summing the quartile points from the MIPS (Mental Stress Ischemia Prognosis Study) to yield a cardiovascular reactivity risk score ranging from 0 to 9. The outcome was a composite of cardiovascular death, nonfatal myocardial infarction, and heart failure hospitalizations during follow‐up. A total of 629 participants were included. After adjustment for demographic and traditional risk factors, a blunted hemodynamic response, a greater decrease in flow‐mediated vasodilation, and a greater degree of peripheral vasoconstriction to mental stress were all independently associated with a higher risk of adverse outcomes in both cohorts. By adding the cardiovascular reactivity risk score, the C‐statistic increased significantly by 10% (P<0.001). Conclusions Among individuals with stable coronary artery disease, a risk score derived from cardiovascular reactivity to mental stress was predictive of adverse cardiovascular outcomes beyond traditional cardiovascular risk factors.